The Socioeconomic Effects of the Working Poor Moving to Permanent Dwellings The Case of the Ashray Affordable Housing Pilot Project in India - Burger, Nicholas (RAND Corporation, 2014)
RAND Corporation researchers assessed the socioeconomic effects that moving into permanent dwellings-in particular, into the Ashray Affordable Housing Pilot Project in India-has on the working poor. Low-cost housing projects may help low-income workers and their families improve their living conditions, while still allowing developers to recover their costs.